Study of the Instruments for Financial and Credit Support of Infrastructure Development and the Mechanism of Their Application at the Regional Level - Elena L. GRINKO; Natalya V. ALESINA; Anastasia M. BALAKLEEVA (Communications of International Proceedings, 2021)
The article focuses on the current state and prospects for the development of infrastructure mortgages as one of the instruments of financial and credit support for the infrastructure development at the regional level in modern economic realities within the legal framework of Russia. It also gives an account of the mechanism for its implementation using public-private partnership. Global financing trends in the development of public infrastructure have been analyzed, regulatory and legal problems of implementing the infrastructure mortgage mechanism in Russia have been investigated. The imbalance between the needs of the regions and the sources of financing for infrastructure facilities has been highlighted as the main problem in the development of regional infrastructure. The mechanism of infrastructure mortgage at the regional level has been proposed as an alternative additional instrument for financing public infrastructure, involving the latter in the development of regional development programs.
Keywords: Mortgage; Mortgage Lending; Financial And Credit Mechanisms; Mortgage Development Dynamics In Regions; State Support Of Mortgage Lending Infrastructure Mortgage; Mortgage Loan; Public-Private Partnership; Project Financing; Investment Project; Economic Growth.